2018 IFPRI A-133 (Uniform guide) - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
We have audited the accompanying financial statements of International Food Policy Research Institute (IFPRI), which comprise the statements of financial position as of December 31, 2018 and 2017, the related statements of activities, functional expenses, changes in net assets and cash flows for the years then ended and the related notes to the financial statements (collectively, the financial statements).